142 Monitoring internal load in professional female football players using urine metabolomics. (3rd March 2020) - Quintas, Guillermo; Ferrer, Eva; Reche, Xavier; Rodas, Gil
Abstract : Background: The molecular mechanisms that govern how athletes adapt to training are reflected at the metabolic level as changes in protein concentrations and enzyme activity. Previous studies suggest that metabolomics could be used for individualized monitoring of athletes' physiological response to training. Objective: This study analyzed the association between external load, defined using EPTS-derived variables, and trends in selected metabolic factors in urine among female professional football players throughout one season. Design: Observational longitudinal study Setting: FC Barcelona, Spain Methods: Between July 2018 and April 2019, urine samples and reference EPTS data, acquired using a portable device (WIMU PRO™), were collected from 25 elite professional football players during pre-season (n=12) and after 4 (n=20), 12 (n=24), 31 (n=23) and 39 (n=23) weeks of competition. The dependent variables were urinary metabolites associated with unbalanced oxidative stress and metabolic adaptation to training (amino acids; tryptophan, phenylalanine, and purine metabolism; and lipid peroxidation products of oxidative stress). We used multivariate analysis to test for association between quantitative metabolic profile and EPTS results. Results: Multivariate analysis allowed us to detect subtle changes in the urinary metabolome associated with training involving e.g. methylhistidine, aspartic acid, BCAA (leucine/isoleucine, valine). Conclusions: Improved performance partly depends on the ability of the athlete's working skeletal muscle metabolism to adapt in response to exercise training. Given the large inter- and intra-individual differences in performance for the same training loads, our results show that individualized monitoring of changes in the urinary metabolome could improve monitoring of the athlete's response to the external training load. Further studies are ongoing and are required before this approach can be implemented in the clinical setting.